2009
DOI: 10.1073/pnas.0909114106
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent fusion of MYB and NFIB transcription factor genes in carcinomas of the breast and head and neck

Abstract: The transcription factor gene MYB was identified recently as an oncogene that is rearranged/duplicated in some human leukemias. Here we describe a new mechanism of activation of MYB in human cancer involving gene fusion. We show that the t(6;9)(q22-23;p23-24) translocation in adenoid cystic carcinomas (ACC) of the breast and head and neck consistently results in fusions encoding chimeric transcripts predominantly consisting of MYB exon 14 linked to the last coding exon(s) of NFIB. The minimal common part of MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
639
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 712 publications
(686 citation statements)
references
References 30 publications
21
639
4
4
Order By: Relevance
“…The identification of ETV6-NTRK3 fusion in MASC adds yet another gene fusion to the growing list of chimeric genes of diagnostic importance for salivary gland carcinomas. Previous studies have shown that mucoepidermoid carcinomas are characterized by CRTC1/ CRTC3-MAML2 or EWSR1-POU5F1 fusions [24,25] and adenoid cystic carcinomas by MYB-NFIB fusions [26]. In addition, Antonescu et al [27] recently identified a consistent EWSR1-ATF1 fusion in hyalinizing clear cell carcinoma of minor salivary glands.…”
Section: Resultsmentioning
confidence: 98%
“…The identification of ETV6-NTRK3 fusion in MASC adds yet another gene fusion to the growing list of chimeric genes of diagnostic importance for salivary gland carcinomas. Previous studies have shown that mucoepidermoid carcinomas are characterized by CRTC1/ CRTC3-MAML2 or EWSR1-POU5F1 fusions [24,25] and adenoid cystic carcinomas by MYB-NFIB fusions [26]. In addition, Antonescu et al [27] recently identified a consistent EWSR1-ATF1 fusion in hyalinizing clear cell carcinoma of minor salivary glands.…”
Section: Resultsmentioning
confidence: 98%
“…This is surprising because there is generally strong correlation between transactivation and transformation by c-Myb (Hu et al, 1991), and the importance of functional co-activation by CBP/p300 (Pattabiraman et al, 2009) and menin/MLL (Jin et al, 2010) has been shown. In cancers linked to aberrations involving the MYB locus, increased c-Myb dosage, and hence activity, seems to be a common theme (Clappier et al, 2007;Lahortiga et al, 2007;Persson et al, 2009). Nevertheless, the 2KR and ANAA mutants described here seem to partially dissociate transactivation from transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The MYB locus is rearranged in several human neoplasias, with increased expression as a frequent outcome. This can be caused by translocation, leading to deregulation of the MYB gene, as in childhood T-cell acute lymphoblastic leukemia (Clappier et al, 2007), or stabilization of MYB mRNA, as in adenoid cystic carcinomas of the breast, head and neck (Persson et al, 2009). Local duplication of MYB has also been reported with another subgroup of T-cell acute lymphoblastic leukemia (Clappier et al, 2007;Lahortiga et al, 2007) and in a subgroup of acute myelomonocytic leukemia (Murati et al, 2009).…”
mentioning
confidence: 99%
“…This could be explained by autocrine activation of the receptor driven by concomitant expression of one its ligands, FGF2. This growth factor is upregulated in ACC cells with MYB overexpression and therefore is a candidate downstream effector of this oncoprotein 33, 77. The relevance of FGF signaling to ACC tumorigenesis is further supported by the description of mutations in the FGF14 , FGFR4 , or FGFR2 genes in 4 different tumors 24, 25.…”
Section: Introductionmentioning
confidence: 95%